Book review: An ambitious study on the multiple leaderships of the Global South Open configuration optionsRevista CIDOB d'Afers Internacionals_139 Open configuration options - Oriol Farrés (Revista CIDOB d'Afers Internacionals)
Review of the book: Braveboy-Wagner, Jaqueline Anne. Diplomatic strategies of rising nations in the Global South: the search for leadership and influence . Palgrave McMillan, 2023, 478 págs.